Approximate Solution for Two Machine Flow Shop Scheduling Problem to Minimize the Total Earliness - Abdullah, H. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper proposes a new algorithm (F2SE) and algorithm (Alg(n – 1)) for solving the two-machine flow shop problem with the objective of minimizing total earliness. This complexity result leads us to use an enumeration solution approach for the algorithm (F2SE) and (DM) is more effective than algorithm Alg( n – 1) to obtain approximate solution.